Elementary ESOL and content teachers' resilient co-teaching practices: a long-term analysis. Issue 4 (1st October 2020) - Bauler, Clara V.; Kang, Emily J. S.
ABSTRACT: New York State adopted regulations that mandate collaboration among ESOL and content teachers in integrated periods where ELLs are mainstreamed into general education classes. We documented trends in elementary and ESOL teachers' co-teaching practices across 3 years of state policy implementation. Findings revealed that even with limited co-planning time, teams of co-teachers developed enduring resilient practices. It was apparent that there was no "right" co-teaching model. What seemed to work was more organic types of structures based on the co-teachers' ability to share and implement ideas together. Trends in ELLs' NYSESLAT scores indicated a decrease in the number of students performing at the lowest proficiency levels with a simultaneous increase in the number of students performing at higher proficiency levels. In spite of positive findings, persistent barriers in the form of insufficient co-planning time and curricular constraints impeded co-teaching to fully thrive in the district. Without systemic and consistent structures to place co-teaching and co-planning at the center of ESOL and content area teachers' collaboration, the success of co-teaching was highly dependent on interpersonal relationships and individual motivations. Meaningful transformation of co-teaching practices for ELLs should be the responsibility of all stakeholders, not only teachers.